Impact of mass media on citizens’confidence in the police: strategies for effective communication - O. V. Zueva (Вестник Майкопского государственного технологического университета, 2025)
Introduction. The article analyzes the impact of the media on the level of public trust in the police, as well as the development of effective communication strategies to strengthen this trust. In the context of modern society, the media play a key role in shaping public opinion about the activities of various government institutions, including the police. With the development of digital media and mobile applications, the influence of the media on public trust is becoming more obvious. Positive or negative media coverage can significantly affect public sentiment, and therefore the effectiveness of the police.Materials and methods. Based on the analysis of theoretical and empirical studies by sociologists and media specialists, the author analyzes the mechanisms by which the media influence the level of public trust. Content analysis of publications in digital media and mobile applications has made it possible to identify problematic aspects in the field of posted content. Focus group research has made it possible to note positive trends in the interaction of the police with traditional media.The Research results. The key problems hindering effective communication include: insufficient digital literacy of employees responsible for posting information, lack of interest and understanding of the importance of digital interaction, lack of resources aimed at developing and supporting digital platforms.Discussion and conclusion. The article emphasizes the importance of police interaction with the media, the introduction of feedback mechanisms, improving the level of media literacy of police officers, as well as the importance of open communication in managing citizens’ trust. The author points out the need to adapt communication strategies to the modern realities of the digital space.